2018
DOI: 10.1021/acs.jnatprod.8b00761
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Natural Product Diversity for Fluorophore Discovery: Naturally Occurring Fluorescent Hydroxyanthraquinones from the Marine Crinoid Pterometra venusta

Abstract: Fluorescent small molecules are important tools in many aspects of modern biology. A two-stage evaluation process involving fluorescence screening and live-cell imaging was developed to facilitate the identification of new fluorescent probes from extracts housed within the NCI Natural Products Repository. To this end, over 2000 extracts and prefractionated samples were examined, including an extract from the marine crinoid Pterometra venusta. An optically guided evaluation involving stepwise fluorescence scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Based on the biogenetic consideration, the absolute configuration of C-2′ in 4 should be the same as that of C-2′ in 2 , i.e., ( S ). Additionally, this hypothesis was supported by the same sign of their optical rotations (dextrorotatory), which is based on the report by Singh et al [ 17 ], that 1,3,8-trihydroxy-6-(2′-acetoxyptopyl) anthracene-9,10-dione, isolated from the marine crinoid Pterometra venusta , ([α] 25 D + 40, c 0.05, MeOH) and its deacetylated product ([α] 25 D + 37, c 0.05, MeOH) were both dextrorotatory. Literature search revealed that 4 has never been previously reported.…”
Section: Resultssupporting
confidence: 60%
“…Based on the biogenetic consideration, the absolute configuration of C-2′ in 4 should be the same as that of C-2′ in 2 , i.e., ( S ). Additionally, this hypothesis was supported by the same sign of their optical rotations (dextrorotatory), which is based on the report by Singh et al [ 17 ], that 1,3,8-trihydroxy-6-(2′-acetoxyptopyl) anthracene-9,10-dione, isolated from the marine crinoid Pterometra venusta , ([α] 25 D + 40, c 0.05, MeOH) and its deacetylated product ([α] 25 D + 37, c 0.05, MeOH) were both dextrorotatory. Literature search revealed that 4 has never been previously reported.…”
Section: Resultssupporting
confidence: 60%
“…Acetylated quinones are not common among natural products, especially among echinoderms. However, acetylated anthraquinones have recently been isolated from the crinoid Pterometra venusta [ 14 ]. Gymnochrome G ( 1 ) and H ( 2 ) represent the first acetylated phenanthroperylene quinone pigments.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the prevalence of uorescent molecules in natural product extracts has also provided an opportunity for development of new chemical probes with novel uorophores. 103 Another potential challenge posed in cell-based HTS is the presence of non-specic cytotoxic compounds. Although it is difficult to nd solid corroboration, anecdotally there tends to be an expectation that cytotoxic extracts may be chemically and biologically more diverse than innocuous extracts.…”
Section: Assay Optimization For Screening Natural Products In Cell-bamentioning
confidence: 99%
“…The development of lead molecules from screening hits derived from natural products is aided by the analysis of structural analogs and establishment of SAR for active compounds oen produced in the same source organism. 99,103,109 Analog development for isolated natural products can also oen be addressed by the development of synthetic methods. 52,100,101 Rocaglamide, from Aglaia extracts, was found to be able to sensitize TRAIL-resistant cells to TRAILinduced apoptosis.…”
Section: Active Sample Prioritizationmentioning
confidence: 99%